Public Prosecution between Dependency and Independence: A Study in the French Experience. - عبدلي, سفيان (Milev Journal of Research and Studies, 2020)
The prosecution was hierarchically linked to the executive authority with the justification for implementing the state penal policy; The government sets the parameters for this policy and is politically responsible to Parliament.While it has been stated that the prosecution should apply the penal policy defined by the government, within the framework of hierarchical subordination, it should not be forgotten that members of the prosecution are ultimately judges. They must act in a impartial and objective manner because the judiciary's independence is not only that of judges but also that of members of the prosecution. Although the idea of subordination of the prosecution to the executive power is firmly based on the logic of democratic legitimacy and framed by the principle of balance between the authorities. the prevailing trend today is to remove the judicial power from all these conflicts. Political, and there is no will - especially within the European judiciary - to link the judicial institution to a world of politics, especially executive power.Due to the influence of the decisions of the European Court of Human Rights, it is no longer acceptable today to have a public prosecutor structurally affiliated with the judiciary and functionally subordinate to the executive power.